The health system benefits of attending an HIV/AIDS conference - Alet Bosman; Jacqueline Wolvaardt (South African Medical Association, 2017)
Background. Although abstract-driven scientific conferences are expensive, little has been written about their benefits and whether attendance influences delegates’ actions.Objective. To explore possible benefits of conference attendance among 97 scholarship recipients at the International Conference on AIDS and Sexually Transmitted Infections in Africa (ICASA) 2013.Methods. A cross-sectional study was conducted. Data were collected via an online survey before the start and on the last day of the conference, and 5 months after the conference.Results. Scholarship recipients represented 27 countries and were between 20 and >60 years of age. The majority of respondents were between 26 and 40 years old, were male, and were researchers/scientists or advocates/activists. Respondents reported that they attended ICASA 2013 to learn more about tuberculosis/HIV/AIDS/sexually transmitted infections and networking opportunities. The majority reported that they gained professionally from attending ICASA 2013 and made ‘new contacts and opportunities for partnership and collaboration’ and ‘new ideas/directions for new project(s)’. Respondents identified ways in which they intended to use what they had learnt at the conference. Five months later respondents reported that they, their colleagues, managers and/or partners were motivated with regard to their HIV work and had shared information, best practices and/or skills gained. The majority had implemented best practices or innovations and retained professional contact with someone they met at ICASA 2013.Conclusion. Conference scholarship programmes provide opportunities for learning and networking and may translate into partnerships or joint ventures, which may result in the implementation of innovations and best practices. Such programmes may also lead to skills transfer, which could strengthen workforce capacity and health systems.